Catalisadores à base de Mo, NiMo e CoMo suportados sobre y-Alumina ou Al-MCM-41 - Avaliação na hidrodessulfurização do dibenzotiofeno - Baston, Eduardo Prado (2007)
The effect of the γ Al2O3 synthesized by Sol-Gel method and Al-MCM-41 mesoporous molecular sieves used as supports in the preparation of Mo, NiMo and CoMo catalysts was studied. The activity and selectivity of the catalysts were evaluated through the HDS of DBT using a batch reactor operated at 300 ºC under 6,9 MPa of H2. TG/DTG, chemical analysis, XRD, N2 adsorption/desorption, DRS-UVVIS and H2-TPR were used to sample characterization. XRD and N2 adsorption/desorption data showed that the method used to synthesize Al-MCM-41 allowed the preparation of solids with well ordered mesoporous array, high specific surface area and mean pore diameter of 2,87 nm. Otherwise, the γ Al2O3 prepared via Sol-Gel procedure presented a higher specific surface area than a commercial γ Al2O3. After the Mo, Ni or Co impregnation, the supports preserved their structural properties, however a diminution in their specific surface are was observed. The effect of the metal impregnation was more pronounced in the catalysts supported on γ Al2O3, leading to a more diminution of the area and in the mean pore diameter. XRD, H2-TPR and DRS-UVVIS data evidenced the presence of MoO3, NiMoO4 or CoMoO4 species in prepared catalysts, which are the precursors in the obtention of the active phase after sulfidation. The catalysts were highly actives in the HDS of DBT, with the bimetallic ones (Mo and Ni (or Co)) presenting high conversion values (higher than 70 %) after 8 hours on stream. That behavior confirmed the important role of Ni and Co as promoter in the HDS of DBT. The occurrence of the cracking reaction was influenced by the specific surface area of the support and the nature, strength and distribution of the acid sites, with Al-MCM-41 being more active. Cyclohexylbenzene (CHB) produced by DBT hydrogenation/desulfurization (HYD) or Biphenyl produced by direct desulfurization (DDS) were the main reaction products. Nevertheless, the Mo and NiMo catalysts favored the HYD route, due to the more hydrogenation capability of the Ni. On the other hand, the CoMo catalysts were more effective in the DDS route.